Salamander climbing behavior varies among species and is correlated with community composition. (4th April 2018) - Mezebish, Tori D; Blackman, August; Novarro, Alexander J
Abstract : How do salamander species live together in densely populated communities? One way they may coexist is by dividing space through climbing behavior. We found that different-sized species climb on plants at different rates. For some species, climbing frequency is correlated with the number of competitors in the community, suggesting that climbing behavior may be a means of reducing competitive interactions. Thus, climbable structures such as plants could facilitate larger population sizes and greater species diversity. Abstract: Species coexistence is often facilitated by behavioral strategies that minimize competition for limited resources. Terrestrial, lungless salamanders (genus Plethodon ) coexist in predictable assemblages of body size guilds, but little is known about the behavioral mechanisms that promote such coexistence. Here, we considered the hypothesis that Plethodon salamanders use climbing behavior to reduce competitive interactions, thereby promoting coexistence through spatial partitioning. To explore this hypothesis, we quantified the frequency of climbing behavior at field sites where small-bodied ( P. cinereus ) and large-bodied ( P. glutinosus ) species are always present, but an intermediate-bodied species ( P. montanus ) is either absent, introduced, or native. We observed that climbing behavior varied among size guilds so that the smallest species climbed most frequently, followed by the intermediate, and then the large species. Further, we identified several correlates of climbing behavior that may be shaped by intraspecific and interspecific competition. Climbing frequency was positively correlated with intraspecific competition and negatively correlated with interspecific competition in the small species, unrelated to competition in the intermediate species, and positively correlated with interspecific competition in the large species. Our results suggest that Plethodon size guilds might differentially utilize climbing behavior to facilitate spatial partitioning in dense populations and communities. Further, we show how competition intensity can shape the behavior of cohabitating species, and ultimately provide insight into how behavioral plasticity and microhabitat partitioning can promote species coexistence.